Pengaruh Profitabilitas, Solvabilitas, Dan Reputasi Kantor Akuntan Publik Terhadap Audit Delay - Annisa; Ulfi Maryati; Eka Siskawati (Jurusan Akuntansi Politeknik Negeri Padang, 2022)
This study aims to empirically examine the effect of profitability, solvency, and reputation of a Public Accounting Firm (KAP) on audit delay. The control variables used in this study are firm size, firm age, and audit opinion. The dependent in this study is audit delay which is measured quantitatively in the number of days using the difference between the issuance date of the financial statements and the issuance of the audit report variables. The research population is Food and Beverage Companies in the non-Cyclical Consumer Sectors which are listed on the Indonesia Stock Exchange (IDX) during 2019-2021. Determination of the sample in this study using purposive sampling and obtained a sample of 21 Food and Beverage Companies. Data analysis used multiple linear regression analysis with SPSS version 25. The results of this study indicate that profitability has no significant effect on audit delay, while solvency and reputation of KAP have a negative but significant effect on audit delay. The control variables of firm size and audit opinion have no significant effect on audit delay, while firm age has a negative but significant effect on audit delay.